2008
DOI: 10.1021/jp076999v
|View full text |Cite
|
Sign up to set email alerts
|

Reactivity of LiBH4:  In Situ Synchrotron Radiation Powder X-ray Diffraction Study

Abstract: Lithium tetrahydridoboranate (LiBH 4 ) may be a potentially interesting material for hydrogen storage, but in order to absorb and desorb hydrogen routinely and reversibly, the kinetics and thermodynamics need to be improved significantly. A priori, this material has one of the highest theoretical gravimetric hydrogen contents, 18.5 wt %, but unfortunately for practical applications, hydrogen release occurs at too high temperature in a non-reversible way. By means of in situ synchrotron radiation powder X-ray d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
118
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 128 publications
(123 citation statements)
references
References 37 publications
5
118
0
Order By: Relevance
“…Indeed, Au et al 41 and Yang et al 42 have screened a batch of additives, and if one classifies them with respect to their Pauling electronegativities, the sequence obtained does not match with their effectiveness in destabilizing the hydride. Evidences of partial substitution came recently from Mosegaard et al 43 They found from an in situ X-ray diffraction study that LiCl, formed from the reduction reaction of TiCl 3 by LiBH 4 , is dissolved to some extent in the structure of solid lithium borohydride at temperatures above ∼100°C, giving an example of a chemical substitution in LiBH 4 . It is also possible to synthesize by wet chemistry ternary metal borohydrides, 44 and recently a computational screening study has been performed to identify which ternary metal borohydrides may form stable alloys with promising decomposition energies.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, Au et al 41 and Yang et al 42 have screened a batch of additives, and if one classifies them with respect to their Pauling electronegativities, the sequence obtained does not match with their effectiveness in destabilizing the hydride. Evidences of partial substitution came recently from Mosegaard et al 43 They found from an in situ X-ray diffraction study that LiCl, formed from the reduction reaction of TiCl 3 by LiBH 4 , is dissolved to some extent in the structure of solid lithium borohydride at temperatures above ∼100°C, giving an example of a chemical substitution in LiBH 4 . It is also possible to synthesize by wet chemistry ternary metal borohydrides, 44 and recently a computational screening study has been performed to identify which ternary metal borohydrides may form stable alloys with promising decomposition energies.…”
Section: Discussionmentioning
confidence: 99%
“…Since Bogdanovic et al found that the addition of Ti-based compounds significantly promoted the dehydrogenation-rehydrogenation reactions of NaAlH 4 [193], the development of complex hydrides for hydrogen storage has significantly increased. Stimulated by this finding, a large number of additives from oxides, halides, metals, and carbon-based materials to M(BH 4 ) n have been examined [19,20,58,87,101,130,144,150,161,168,170,171,191,[194][195][196][197][198][199][200][201][202][203][204][205][206][207][208][209][210]; the corresponding dehydrogenation and rehydrogenation properties are summarized in Table 5. For instance, the most effective additive for LiBH 4 was found to be the mixture of 0.2 MgCl 2 + 0.1 TiCl 3 , in which approximately 5 mass% of hydrogen was released from 333 K and 4.5 mass% of hydrogen was rehydrogenated at 873 K in 7 MPa H 2 [195].…”
Section: Promoting Kineticsmentioning
confidence: 99%
“…13,14 Anion substitu-tion in metal borohydride materials was reported for LiBH 4 -LiX, where X = Cl, Br, and I in NaBH 4 -NaCl, in Ca(BH 4 ) 2 -CaX 2 , X = Cl and I, and in Mg(BH 4 ) 2 -MgX 2 , X = Cl and Br. [15][16][17][18][19][20][21][22][23][24] The change in the hydrogen storage properties of anion-substituted metal borohydride using the heavier halides, Cl, Br or I, is small and may lead to a stabilization, which tends to facilitate hydrogen absorption. 18,19,24 In contrast, calculations reveal that fluorine substitution in LiBH 4 is not thermodynamically favored but should indeed provide a destabilization of lithium borohydride.…”
Section: Introductionmentioning
confidence: 99%